PENERAPAN STRATEGI PEMBELAJARAN CROME BERBANTUAN LKS UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - Andriani, Ni Kadek Ari; Adnyana, Putu Budi; Heny, Ajeng Purnama (JURNAL BIOEDUCATION, 2024)
This research aims to determine the application of the student worksheet-assisted CROME learning strategy to improve students' cognitive learning outcomes on human excretory system material and to determine the difference between the application of the student worksheet-assisted CROME learning strategy and conventional learning strategies on students' cognitive learning outcomes. The type of research is quasi-experimental with a non-equivalent control-group design research design. The research sample was class XI students at SMA Negeri 2 Bangli who were chosen randomly by lottery. Based on the results of random class selection, class the method in this research uses multiple choice tests related to cognitive process dimensions. Data were analyzed using quantitative descriptive analysis and Anacova (Analysis of Covariance) to determine the application of the student worksheet-assisted CROME learning strategy to improve students' cognitive learning outcomes on human excretory system material and to determine the difference between the application of the student worksheet-assisted CROME learning strategy and conventional learning strategies on students' cognitive learning outcomes. The results of the hypothesis test show that the p value (0.0001) < 0.05 and the Partial Eta Squared (effect size) value obtained is 0.320, which means that the application of the CROME learning strategy assisted by worksheets on the human excretory system material improves students' cognitive learning outcomes by 32 %, with an increase percentage in the experimental class of 62% and the control class of 34%. Based on this data, it proves that there are differences in cognitive learning outcomes between students who were taught using the CROME learning strategy assisted by worksheets on the human excretory system and conventional learning strategies